TECHNICAL EFFICIENCY OF CIHERANG RICE FARMING IN EAST LENTENG VILLAGE, LENTENG DISTRICT, SUMENEP REGENCY - Silviana Dewi; Resti Prastika Destiarni (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2023)
The food crop subsector has a very important role because the increasing population in Indonesia can affect food fulfillment and food security. One of the most dominant staple foods is rice, so rice farming is still the mainstay of farmers to fulfill the needs of households and communities. East Lenteng Village is one of the villages that plant ciherang rice 2 times a year. However, the productivity of ciherang rice in East Lenteng village did not reach 8.5 tons / ha. The purpose of this study is to analyze the factors that affect the production yield of ciherang rice farmers and analyze the level of efficiency of ciherang rice farming in East Lenteng Village. The analysis method of this study is the Cobb Douglas Production Function through Frontier Stochastic approach. The data used are primary data obtained from direct interviews with farmers using structured questionnaires. The results showed that there are 3 factors that affect the yield of ciherang rice production, they were planting area, number of seeds, and the amount of organic fertilizer and 88.4% of farmers in East Lenteng Village have achieved technical efficiency. Farmers can increase their productivity by using quality rice seeds.  In addition, farmers can use fertilizers according to recommendations such as the use of organic fertilizer as much as 2 tons / ha, NPK Phonska fertilizer 150 kg / ha, Urea 200 kg / ha and ZA fertilizer 150 kg / ha.